A novel N, Fe-Decorated carbon nanotube/carbon nanosheet architecture for efficient CO2 reduction. (20th May 2018) - Pan, Fuping; Zhao, Huilei; Deng, Wei; Feng, Xuhui; Li, Ying
Abstract: The development of high-performance electrocatalysts for CO2 reduction reaction (CO2RR) is a prerequisite to enable CO2 -to-fuels electrolysis a feasible solution for reaching a carbon neutral cycle and producing value-added fuels. In this work, we report the design of a novel nanostructured electrocatalyst consisting of carbon nanotube/carbon nanosheet architecture with N and Fe doping (NFe-CNT/CNS) by a SiO2 -protected calcination strategy. The hierarchical structure of CNT/CNS affords abundant N-induced defects and Fe−N species as highly active sites and facilitates mass transportation, and carbon nanotube also offers a smooth route for charge transfer in the CO2RR process. These synergistic merits afford NFe-CNT/CNS with high performance for CO2RR in terms of a maximum FE of 69% at a low overpotential of 0.48 V, a small Tafel slope of 89 mV dec −1, and enhanced stability for CO production in aqueous solution. The findings demonstrate that the integration of structural design and dopants optimization is effective to boost electrocatalytic activity of nanocarbons for CO2 reduction. Graphical abstract: Highlights: A SiO2 -protected calcination strategy to fabricate CNT/CNS architecture. Realize the facile formation of Fe−N complex as active species in CO2RR. Achieve enhanced activity and stability for the reduction of CO2 to CO. Synergy of hierarchical CNT/CNS and dense Fe−N responsible for high activity.